On reading books to children parents and teachers - Van Kleeck, Anne.; Stahl, Steven A.; Bauer, Eurydice Bouchereau (Mahwah, N.J. L. Erlbaum Associates, 2003)
On Reading Books to Children: Parents and Teachers brings together in one volume current research on adult book reading to children. The authors, drawn from around the world, are key researchers and eminent scholars from the fields of reading.
Book sharing in families -- Social-emotional requisites for learning to read / Adriana G. Bus -- Learning words from books / Jeanne De Temple and Catherine E. Snow -- Diversity in adults styles of reading books to children / Elaine Reese, Adell Cox, Diana Harte, and Helena McAnally -- Book sharing with preschoolers with language delays / Anne van Kleeck and Judith Vander Woude -- Storybook reading in the classroom -- A framework for examining book reading in early childhood classrooms / David K. Dickinson, Allyssa McCabe, and Louisa Anastasopoulos -- Reading aloud to young children as a classroom instructional activity: insights from research and practice / William H. Teale -- The nature of storybook reading in the elementary school : current practices / Lesley Mandel Morrow and Rebecca Brittain -- Taking advantage of read-alouds to help children make sense of decontextualized language / Margaret G. McKeown and Isabel L. Beck -- Dialogic reading : a shared picture book reading intervention for preschoolers / Andrea A. Zevenbergen and Grover J. Whitehurst -- Storybook sharing as cultural practice -- Storybook reading in a multicultural society : critical perspectives / Jim Anderson, Ann Anderson, Jacqueline Lynch, and Jon Shapiro -- Reading, homes, and families : from postmodern to modern? / Victoria Carrington and Allan Luke -- Storybook reading and young bilingual children : a review of the literature / Rosalinda B. Barrera and Eurydice Bouchereau Bauer -- Where do we go from here? -- Research on book sharing : another critical look / Anne van Kleeck -- Joint reading as a context : explicating the ways context is created by participants / A. D. Pellegrini and Lee Galda -- Parent-child storybook reading as a complex adaptive system : or an igloo is a house for bears / David B. Yaden, Jr. -- What do we expect storybook reading to do? How storybook reading impacts word recognition / Steven A. Stahl.
Keywords: Oral reading; Storytelling; Children -- Books and reading